2015
DOI: 10.1557/jmr.2015.320
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acetylene as a dielectric on modification of TiNi-based shape memory alloys by dry EDM

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Kolli M et al [91] showed the impact of graphite powder with the dielectric medium on EDM of titanium alloy. Huang TS et al [92] made a surface modification on NiTi alloy with acetylene and nitrogen gas as a dielectric medium to improve tribological behavior. Yu YT et al [93] made a study on improving the presence of Calcium and phosphorus on Ti implants by using gas-assist dielectric medium.…”
Section: Dielectric Fluidmentioning
confidence: 99%
“…Kolli M et al [91] showed the impact of graphite powder with the dielectric medium on EDM of titanium alloy. Huang TS et al [92] made a surface modification on NiTi alloy with acetylene and nitrogen gas as a dielectric medium to improve tribological behavior. Yu YT et al [93] made a study on improving the presence of Calcium and phosphorus on Ti implants by using gas-assist dielectric medium.…”
Section: Dielectric Fluidmentioning
confidence: 99%